Motivational Vigor in Parkinson's Disease Requires the Short and Long Duration Response to Levodopa - Brissenden, James A.; Scerbak, Teresa; Albin, Roger L.; Lee, Taraz G. (Movement disorders, 2024)
Background Impaired movement vigor (bradykinesia) is a cardinal feature of Parkinson's disease (PD) and hypothesized to result from abnormal motivational processes—impaired motivation‐vigor coupling. Dopamine replacement therapy (DRT) improves bradykinesia, but the response to DRT is multifaceted, comprising a short‐duration response (SDR) and a long‐duration response (LDR) only manifesting with chronic treatment. Prior experiments assessing motivation‐vigor coupling in PD used chronically treated subjects, obscuring the roles of the SDR and LDR. Methods To disambiguate the SDR and LDR, 11 de novo PD subjects (6 male [M]:5 female [F]; mean age, 67) were studied before treatment, after an acute levodopa (l‐dopa) dose, and in both the practical “off” (LDR) and “on” (LDR + SDR) states after chronic stable treatment. At each visit, subjects were characterized with a standard battery including the Movement Disorder Society‐Sponsored Revision of the Unified Parkinson's Disease Rating Scale (MDS‐UPDRS) and an incentivized joystick task to assess motor performance in response to varying rewards. Results l‐Dopa induced a robust SDR and LDR, with further improvement in the combined SDR + LDR state. At baseline, after acute treatment (SDR), and after LDR induction, subjects did not exhibit the normal increase in movement speed with increasing reward. Only in the combined SDR + LDR state was there restoration of motivation‐vigor coupling. Conclusions Although consistent with prior results in chronically treated PD subjects, the significant improvement in motor performance observed with the SDR and LDR suggests that bradykinesia is not solely secondary to deficient modulation of motivational processes. © 2023 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.